The Effect of Art Expertise on Eye Fixation-Related Potentials During Aesthetic Judgment Task in Focal and Ambient Modes - Fudali-Czyż, Agnieszka; Francuz, Piotr; Augustynowicz, Paweł (Frontiers in Psychology, 2018)
This study aims to verify the hypotheses concerning the effect of aesthetic evaluation of paintings and arts expertise on early eye fixation-related potentials (EFRPs, e.g., P1, N1, and P2), recorded in two modes of visual processing, ambient and focal. The ambient mode is related to bottom-up, preattentive exploring of visual organization of the scene, and the focal mode is pertaining to top-down, focused attention on the objects. Focal and ambient modes were obtained by averaging post-saccadic cerebral activity about the beginning of long eye fixations followed by short saccades and short fixations followed by long saccades, respectively. Thirty experts with formal training in visual arts and 32 non-experts freely viewed 150 figurative paintings presented for 20 seconds, each. After viewing the painting, the participant answered the question: “Is this painting beautiful?” It was found that the aesthetic evaluation task and expertise modulate the amplitude of the eye fixation-related potentials but only when the focal mode of processing is considered. The expertise effect was mirrored at the parietal P2 component (160–230ms) and the frontal P2 (140–190ms) time windows related to the beginning of long fixations followed by short saccades, exclusively. Long fixations of experts had a higher amplitude of the parietal P2 recorded from right electrodes than non-experts. In the group of experts, the frontal P2 was higher for long fixations on not beautiful paintings in comparison to long fixation on beautiful paintings. Moreover, in focal mode, there were higher occipital lambda response (70–120ms) and N1-P2 complex (135–235ms) for not beautiful than beautiful paintings. The obtained results were discussed in the light of the theory and results of the ERP and the EFRP research about the aesthetic evaluation of paintings by art experts and non-experts.